Active packaging of chitosan film modified with basil oil encapsulated in silica nanoparticles as an alternate for plastic packaging materials. (February 2023) - Sultan, Maha; Abdelhakim, A.A.; Nassar, Mona; Hassan, Youssef R.
Abstract: Active packaging based on biomaterials and essential oils is an alternate for plastic ones. But, essential oils are chemically and physiologically labile, and they have strong scents, limiting their use as antimicrobial additives in food. Thus, in this investigation, basil oil was encapsulated in silica nanoparticles (basil oil@SiNPs) and combined with chitosan films (basil oil@SiNPs@chitosan). Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), X-ray diffraction (XRD), surface area and Brunauer-Emmett-Teller (BET) analysis, encapsulation and loading % were used to evaluate basil oil@SiNPs. The surface area of SiNPs decreased from 59.006 to 43.86 cm 2 /g due to basil oil encapsulation. The encapsulation and loading % were 81.96, 65.87, 48.48 and 43.13, 37.64, 33.44% for 2, 1.5, and 1 mL of basil oil, respectively. Fourier-transform infrared (FT-IR), XRD, thermogravimetric analysis (TG), mechanical, wettability, water vapor permeability (WVP), oxygen permeability (OP) features; water vapor sorption isotherms and antimicrobial inhibition tests were used to describe the produced basil oil@SiNPs@chitosan films. Water contact angles and activation energy increased from 89.0° to 110.9° and −11.97 to −20.40 kJ/mol, respectively after addition of basil oil@SiNPs. However, WVP decreased from 5.9580 × 10 −1 ±0.33 to 4.2413 × 10 −1 ±0.55 g.mm.m −2 .h −1 .kPa −1 and OP increased from 4.094 × 10 −4 ±0.52 to 6.715 × 10 −5 ±0.32 (g.m −2 .day −1 .atm −1 ). The four models Guggenheim–Anderson–de Boer (GAB), Smith, Henderson and SIPSI were suitable for describing the moisture sorption of basil oil@SiNPs@chitosan films. Basil oil@SiNPs has antimicrobial inhibition against Gram positive and negative bacteria, pathogenic yeast.